Enhancing microprocessor immunity to power supply noise with clock-data compensation. - Wong, K.L (IEEE Journal of solid state circuits)
This paper demonstrates an alternative to the conventional wisdom that microprocessors require a flat impedance spectrum across a broad range of frequencies in order to deliver maximum operating frequency. Delivering this impedance requires large amounts of on-die capacitance. We show through extensive analysis techniques that proper co-design of the clock and power distribution networks can relax this requirement, saving the area and leakage power needed for on-die decoupling. Measurements made on 130- and 180-nm processors validate the approach.